Композиційна структура деревних угруповань у рівнинно-пейзажному районі Тростянецького парку - Medvedev, V.A.; Iljenko, O.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
The results of researches of basic progress trends and orientation of changes of composition structure of decorative groups of flatly-landscape part of Dendropark Trostjanets in the period from 1949 to 2007 are presented.